Performance Assessment of Using Docker for Selected MPI Applications in a Parallel Environment Based on Commodity Hardware - Tomasz Kononowicz; Paweł Czarnul (Applied Sciences, 2022)
In the paper, we perform detailed performance analysis of three parallel MPI applications run in a parallel environment based on commodity hardware, using Docker and bare-metal configurations. The testbed applications are representative of the most typical parallel processing paradigms: master–slave, geometric Single Program Multiple Data (SPMD) as well as divide-and-conquer and feature characteristic computational and communication schemes. We perform analysis selecting best configurations considering various optimization flags for the applications and best execution times and speed-ups in terms of the number of nodes and overhead of the virtualized environment. We have concluded that for the configurations giving the shortest execution times the overheads of Docker versus bare-metal for the applications are as follows: 7.59% for master–slave run using 64 processes (number of physical cores), 15.30% for geometric SPMD run using 128 processes (number of logical cores) and 13.29% for divide-and-conquer run using 256 processes. Finally, we compare results obtained using gcc V9 and V7 compiler versions.